2021
DOI: 10.1002/art.41708
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Patients With Sjögren’s Syndrome and Patients With Systemic Lupus Erythematosus According to Two Shared Immune Cell Signatures, With Potential Therapeutic Implications

Abstract: Objective Similarities in the clinical and laboratory features of primary Sjögren’s syndrome (SS) and systemic lupus erythematosus (SLE) have led to attempts to treat patients with primary SS or SLE with similar biologic therapeutics. However, the results of many clinical trials are disappointing, and no biologic treatments are licensed for use in primary SS, while only a few biologic agents are available to treat SLE patients whose disease has remained refractory to other treatments. With the aim of improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
1
26
0
1
Order By: Relevance
“…Martin-Gutierrez et al [ 33 ] identified an immune signature derived from the analysis of 29 different cell subsets including B and T cells, which was driven by five distinct cell subsets: transitional Bm2′ cells, late memory Bm5 cells, IgD-CD27-B cells, and CD8 + naive and CD8 + Tem which differentiated between pSS patients and matched HCs. Moreover, they identified a shared immunological profile across three disease phenotypes: systemic lupus erythematosus (SLE), pSS and SLE associated with SS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin-Gutierrez et al [ 33 ] identified an immune signature derived from the analysis of 29 different cell subsets including B and T cells, which was driven by five distinct cell subsets: transitional Bm2′ cells, late memory Bm5 cells, IgD-CD27-B cells, and CD8 + naive and CD8 + Tem which differentiated between pSS patients and matched HCs. Moreover, they identified a shared immunological profile across three disease phenotypes: systemic lupus erythematosus (SLE), pSS and SLE associated with SS.…”
Section: Resultsmentioning
confidence: 99%
“…The main players seem to be activated CD8 + T cells, terminally differentiated plasma cells, and activated epithelial cells in biopsies, whereas the peripheral blood signatures comprised high numbers of activated CD4 + , CD8 + T cells. Although these signatures were not perfectly validated across various studies [ 30 , 33 ], some correlated with serological and clinical parameters, suggesting a potential clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent study of primary Sjögren’s syndrome (pSS) and SLE ( Martin-Gutierrez et al, 2021 ), researchers applied supervised ML models to identify shared immunological characteristics between pSS and SLE. These two diseases share some clinical and laboratory features, despite differences in disease pathogenesis and overall clinical presentation, leading to a distinct diagnostic label ( Pasoto et al, 2019 ).…”
Section: Applicationsmentioning
confidence: 99%
“…The process of drug repurposing is much conserved by renouncing the standard drug development pipeline approach and investigating similarities between various disease processes potentially targeted by the same therapeutic interventions, so that new effective treatments can be delivered faster to patients. This is a more cost-effective approach which led in recent years to the testing and licensing of similar classes of therapeutic agents across many immune-mediated chronic inflammatory diseases ( March-Vila et al, 2017 ; Balasundaram et al, 2019 ; Gilvary et al, 2020 ; Martin-Gutierrez et al, 2021 ). In a recent study of computational drug repurposing, researchers developed a ML (Gradient Boosting model) approach, Creating A Translational Network for Indication Prediction (CATNIP) which can effectively connect similar drugs by solely analysing the biological and chemical data of the molecule without the knowledge of the current therapeutic disease applications of the drug ( Gilvary et al, 2020 ).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation